Сontrol of rovs in the mode of combined application - Nadtochii, Viktor A. (My University, 2014)
The task of the automatic control of the marine mobile system of the «carrier vessel – ROV» type in the combined application mode of the ROV group is formulated. Its urgency is caused by the need to inspect the large harbour areas in the shortest time possible and document underwater enities with high reliability. The group mode of the ROVs application can become a basis of the development of the new technology for carrying out marine search-andrescue operations. It is determined that the marine mobile system of the «carrier vessel – ROV» type in the mode of combined application is new entity of the automatic operation and requires developing special control structures and algorithms. The generalised structure of the system of the automatic operation of the group of marine mobile vehicles of «carrier vessel – ROV» the type is suggested and four basic stages of its work are formulated.
Nadtochii, Viktor A. Сontrol of rovs in the mode of combined application = Керування самохідними прив’язними підводними системами у режимі комбінованого застосування / Viktor A. Nadtochii // Вісн. НУК. – Миколаїв, 2014. – № 1. – Режим доступа: http://evn.nuos.edu.ua/article/view/39855/35989
Keywords: ROV; automatic control; operation mode; control algorithm